Properties of butadiene-styrene latexes modified by silicon surface-active substances - I. A. Gritskova; N. I. Prokopov; T. S. Solovyeva; E. V. Matveev; A. N. Lobanov; A. S. Birlov (Тонкие химические технологии)
The properties of butadiene-styrene latexes, stabylized by the mixes of surface-active substances included silicon SAS, practically unsolved in water, were investigated. It was shown that they are characterized by low foaming, practically unswollen in water and stable in the solutions of electrolites